IMPROVING THE STUDENTS SPEAKING SKILL THROUGH PICTURE AT THE EIGHT GRADE STUDENTS OF MTs NEGERI 1 BOLAANG MONGONDOW TIMUR - Andi Mukarramah Nagauleng; Fadhlan Saini Saini; Indah Wardaty Saud; Hakimin Z. Mamonto (British : Jurnal Bahasa dan Sastra Inggris, 2021)
AbstractThis study aims to improve the speaking skills through pictures at the eighth-grade students of MTs Negeri 1 Bolaang Mongondow Timur. This research is classified as a classroom action research. It was conducted in two cycles, each of which held four sessions in the first cycle and two in the second cycle. The subjects of this study were 25 students of class VIII C MTs Negeri 1 Bolaang Mongondow Timur. It used qualitative and quantitative data collecting techniques. Qualitative data obtained through observation and interviews to students and English teachers.  Data was in the form of field notes and interview transcripts, while quantitative data derived from tests (pre-test and post-test) and questionnaires. Besides, this study applies several triangulation techniques, such as time triangulation, researcher triangulation, and data triangulation. The actions carried out in this study used pictures in the teaching and learning process of speaking, applying image-based activities, giving feedback to students’  performances, accustoming students to open dictionaries, giving handouts as daily material, and giving gifts to some active students. The results showed that the pictures application in the teaching and learning process of speaking is believed to be effective for improving students’ speaking skills. Also it showed that improvements in the teaching and learning process affected the improvement of students’ speaking skills. Students’ speaking skills are measured quantitatively. The results revealed that the average score of students’ speaking performance increased from 51.5 in the pre-test to 71.2 in the post-test. The gained score of students’ speaking skills is 19.7. Key Words: improving, students speaking skill, picture